KINERJA GURU DALAM IMPLEMENTASI KURIKULUM 2013 PADA SMA NEGERI 5 LHOKSEUMAWE - Haslina, Yusrizal, Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
ABSTRACT: Teacher performance is a necessity in improving the quality of learning service involving the implementation of a curriculum to all subject components. A curriculum is a collection of contents, objectives, and methods used by teachers to achieve education objectives at schools. The purpose of this study was to know the understanding, implementation, and obstacle faced by teachers at State Junior Hight School (SMA Negeri) 05 of Lhokseumawe in implementing of curriculum 2013. To achieve the objectives, descriptive qualitative approach was used in this research. The techniques of data collection used in this study were interview, observation, and documentation study. The procedure of data analysis done were data reduction, data display, and verification. The subjects in this study were principal, vice principal for curriculum and teaching affairs, and teachers. The result of this study showed that: (1) The ability of teachers in planning, implementing and evaluating the learning process and results in Curriculum 2013 has been good but not optimal particular the management of time in learning less effective and the use of ratings K-13 yet authentic, (2) motivation of teachers in the implementation of the K-13 is high when in view of the implementation of the tasks, moral responsibility in teaching, and the need to cooperate with others, (3) commitment and responsibility of teachers in the implementation of the K-13 also looks good to show their personality, dedication, and high loyalty to the task of teaching, (4) supporting factors and obstacles in the implementation of Curriculum 2013, among others; (A) coordination undertaken by the principal to the realization of the implementation of the K-13 is right on target, (b) good communication between the various parts in the implementation of Curriculum 2013 has been carried out, (c), but supervision of the school principal and teacher assistant for teachers SMAN 5 Lhokseumawe not optimal in learning and assessment process.Keywords: Teacher Performance, Curriculum 2013ABSTRAK: Kinerja guru menjadi suatu keharusan dalam peningkatkan kualitas layanan pembelajaran yang mencakup pelaksanaan kurikulum untuk semua komponen mata pembelajaran. Kurikulum merupakan kumpulan; isi, tujuan, dan cara yang digunakan oleh guru untuk mencapai tujuan pendidikan di sekolah. Penelitian ini bertujuan untuk mengetahui kinerja guru dan hambatan yang dihadapi guru SMA Negeri 5 Lhokseumawe dalam implementasi Kurikulum 2013. Untuk mencapai tujuan tersebut, penelitian ini mengunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumentasi. Prosedur analisis data adalah reduksi data, display data, dan verifikasi data. Sedangkan subjek penelitian adalah pengawas sekolah, kepala sekolah, wakil kepala sekolah bidang kurikulum, guru pendamping K-13 dan guru mata pelajaran. Hasil penelitian menunjukkan bahwa: (1) Kemampuan guru dalam perencanaan, pelaksanaan, dan penilaian proses dan hasil pembelajaran dalam Kurikulum 2013 sudah baik namun belum optimal dalam perencanaan, proses pembelajaran dan penilaian khususnya pengelolaan waktu dalam pembelajaran kurang efektif dan penggunaan penilaian K-13 belum autentik. (2) Motivasi guru dalam implementasi K-13 sudah tinggi bila dilihat dari pelaksanaan tugas, tanggung jawab moral dalam mengajar, dan kebutuhan bekerjasama dengan orang lain. (3) Komitmen dan tanggung jawab guru dalam implementasi K-13 juga terlihat baik dengan menunjukkan kepribadian, dedikasi, dan loyalitas yang tinggi terhadap tugas mengajar. (4) faktor pendukung dan penghambat dalam implementasi Kurikulum 2013 antara lain: (a) koodinasi yang dilakukan oleh kepala sekolah untuk terwujudnya penerapan K-13 sudah tepat sasaran (b) komunikasi yang baik antar berbagai bagian dalam pelaksanaan Kurikulum 2013 sudah dilakukan (c) namun supervisi kepala sekolah dan guru pendamping terhadap guru SMAN 5 Lhokseumawe belum optimal dalam proses pembelajaran dan penilaian.Kata kunci:Kinerja Guru dan implementasi Kurikulum 2013